COUNTERING ISLAMOPHOBIA IN THE DIGITAL AGE: A SOCIOLINGUISTIC AND MEDIA ANALYSIS - Saifuddin Zuhri; Cholid Fadil (Penelitian dan Pengembangan Ilmu, 2025)
Digital media plays a crucial role in shaping public perceptions and accelerating Islamophobia through hate speech, stereotypes, and negative representations. Anti-Muslim incidents have increased significantly, for example in the United Kingdom (5,837 incidents in 2024) and Australia (3,254 incidents from January–July 2025), exacerbated by linguistic bias in AI and the virality of online content. This study systematically reviews the literature on linguistic practices and discursive strategies in Islamophobic narratives in digital media, usingnarrative reviewcritically oriented andCritical Discourse Analysis (CDA). Literature searches were conducted in Scopus, Web of Science, and Google Scholar (2000–2025) and analyzed through thematic synthesis.The results show the use of negative lexical content, metaphors, framing, and othering that reinforce polarized narratives, while algorithms and clickbait journalism accelerate the spread of Islamophobic content. Counternarratives from Muslim communities, including the reappropriation of stigmatizing labels, demonstrate the potential for communal resistance and agency. These findings confirm the relevance of CDA and digital sociolinguistics and provide a basis for effective counternarrative strategies to address online stereotypes and discrimination.